1981
DOI: 10.1159/000179352
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Regulation of TSH Secretion by Superfused Anterior Pituitary Cells

Abstract: Superfused dispersed cells respond rapidly to 2- to 10-min pulses of TRH (10-10 to 10-7M) in a dose-dependent manner. The effects of decreasing the stimulus duration can be overcome by a proportional increase in concentration of TRH. A TRH stimulus of 10 min or greater duration results in a sharp peak in TSH secretion followed by a lower plateau. Somatostatin (10-8M) inhibits the response to TRH (5 X 10-9M). T3 (2.0 µg/dl) inhibits TRH-induced TSH secretion by superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
5
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
(19 reference statements)
5
5
1
Order By: Relevance
“…In contrast to an earlier report [4], the TRH concentration was the only determinant of the amplitude of the acute phase. A 60-fold variation of TRH exposure duration was without obvious effect on the amplitude or duration of the acute phase.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to an earlier report [4], the TRH concentration was the only determinant of the amplitude of the acute phase. A 60-fold variation of TRH exposure duration was without obvious effect on the amplitude or duration of the acute phase.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior reports have not used this or other comparable strategy. We believe that an earlier report [4], which found that an increase in stimulus duration resulted in an increase in secretory response, was probably complicated by chang ing baselines and other longitudinal biases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our data confirm earlier reports [2,3] that it takes > 60 min for Tj to inhibit TRH-induced TSH secretion in vitro. The time required to induce suppression of TRH-induced TSH se cretion was not detectably different between T4 and Ti.…”
Section: Discussionsupporting
confidence: 93%
“…To date, only Tj has been shown to inhibit the secretion of TSH induced by TRH in perifused isolated rat pituitary fragments [2,3]. The present study was undertaken to compare the temporal and quantitative ef fects of T4 and Tj on the TSH response to TRH in this sys tem.…”
mentioning
confidence: 97%